2019
DOI: 10.1177/1932296818821649
|View full text |Cite
|
Sign up to set email alerts
|

What Are Diabetes Patients Versus Health Care Personnel Discussing on Social Media?

Abstract: Use of social media is increasing rapidly, including for health issues and especially for those with diabetes. Among health care personnel there is also a steady increase of social media use. 1,2 This increase in use is generally good for those who are able to actively participate in, or follow the online discussions, but one pattern we see is that patients, health care personnel, and patient organizations discuss diabetes very differently. This can lead to lack of common ground when these stakeholders communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 27 publications
0
23
0
7
Order By: Relevance
“…In a previous study [ 20 ], we surveyed followers of the Norwegian Diabetes Association’s social media channels, and we found that almost all the respondents wanted more content about research and innovation on diabetes in social media groups, preferably in text format. However, other previous studies have reported that social media groups for patients with diabetes mostly shared content about diabetes self-management [ 1 - 4 ], scientific content [ 3 , 4 ], health care services [ 3 , 4 ], diabetes awareness [ 3 , 4 ], personal stories [ 2 ], or humor [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study [ 20 ], we surveyed followers of the Norwegian Diabetes Association’s social media channels, and we found that almost all the respondents wanted more content about research and innovation on diabetes in social media groups, preferably in text format. However, other previous studies have reported that social media groups for patients with diabetes mostly shared content about diabetes self-management [ 1 - 4 ], scientific content [ 3 , 4 ], health care services [ 3 , 4 ], diabetes awareness [ 3 , 4 ], personal stories [ 2 ], or humor [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mean age of participants was 21 years. The majority were female (21), single (34) and had already completed or higher education degree was in progress (21). All participated in the activities until group closure.…”
Section: Resultsmentioning
confidence: 99%
“…(33) Nonetheless, given the possibility of divergence between the information posted in these groups and those recommended, mediation by professionals would minimize dissemination of wrong health practices. (34) In the nurses' daily routine, the use of different technologies can produce significant changes in the self-care capacity of people with DM, highlighting the importance of technical and clinical knowledge of nursing interventions. (3,35) In this sense, the young people studied reported better adherence to treatment with the use of this technology.…”
Section: M20 19 Yearsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finding reliable sources with professional validation of information became an issue with the spread of health information through social media. There is statistically significant inaccuracy in the information posted on social media, which requires verification to ensure safe and accurate information dissemination (Årsand, Bradway, & Gabarron, ). The information disseminated through social media might have positive or adverse health effects as cultural and gender differences affect the body responds to food, home remedies, medication and disease outcomes (Campesi, Franconi, Seghieri, & Meloni, ) and the same recipe might not have the same effect on all people.…”
Section: Discussionmentioning
confidence: 99%